A Note on Sem Studies of Leaf, Pollens and Seeds of the Eremostachys Superba Royle Ex Benth.: a Critically Endangered Medicinal Herb - Panwar, G. S.; Chanu, L. I.; Srivastava, S. K.; Ambrish, K. (Indian Forester, 2014)
Leaf, pollen and seed morphology of Eremostachys superba was studied using scanning electron microscopy (SEM) to facilitate identification of this critically endangered medicinal herb. The SEM analysis of the species showed that the leaf of the species is covered with unicellular sparse indumentum of short or longer simple hairs and more pronounced at the margins. The seeds of E. superba are triradiate with triquetrous surface and a tuft of stiff multicellular hairs are present at the apical end. The pollen grains are tricolpate with reticulate surface.